Analysis of Phytoconstituents and Antimicrobial Properties of Bacopa monnieri (L.) Against Clinical Pathogen: Life Sciences- Botany - Amudha, N.; Magalingam, R.; Selvam, K.; Ambikapathy, V.; Prakash, P. (International Journal of Life Science and Pharma Research, 2023)
There are numerous therapeutic uses for medicinal plants in treating and managing numerous diseases. Traditional medicinal plantswere mostly needed in the current scenario. The world's warmer and wetlands regions are home to the medicinal herb Bacopa monnieri (L.).It has been utilized for ages in Ayurvedic systems. The Bacopa monnieri was one of the traditional medicinal plants. These are commonlycalled "Brahmi," and the Tamil vernacular name is "Neerbrahmmi." It is easy to cultivate and grow in all seasons. These peculiar activeingredients, also known as memory enhancement and phytoconstituents were enriched in this medicinal plant. The present study focused onanalyzing phytoconstituents and the antimicrobial activity of Bacopa monnieri leaves. The efficacy of phytoconstituents on the antimicrobialactivities concerning minimum inhibitory concentrations was performed with different polar and non-polar solvents of the respective plant.The phytoconstituents such as alkaloids, amino acids, coumarins, flavonoids, glycosides, phenols, phlobatannins, quinones, reducing sugars,saponins, steroids, tannins, and terpenoids were recorded, respectively. Antibacterial activity performed with following human clinicalbacteria like Clostridium butyricum, Escherichia coli, Staphylococcus aureus, and Streptococcus pneumoniae, and the antifungal activity against humanclinical such as Aspergillus flavus, A.niger, Aspergillus sp., and Penicillium sp. were determined. Among the two solvent extractions, the aqueousextract showed a more significant result than the benzene extract. According to the MIC, the antimicrobial properties of B.monnieriwithdifferent extracts were analyzed. The very minimum concentration has shown better inhibitions against microbes. The present study exploredthe antimicrobial properties of human clinical pathogens. So, the B.monnieriaqueous extract of leaves was suggested for the treatment ofmicrobial infections.